The Amino Acid Homoarginine Inhibits Atherogenesis by Modulating T-Cell Function. Issue 8 (14th September 2022) - Nitz, Katrin; Lacy, Michael; Bianchini, Mariaelvy; Wichapong, Kanin; Kücükgöze, Irem Avcilar; Bonfiglio, Cecilia A.; Migheli, Roberta; Wu, Yuting; Burger, Carina; Li, Yuanfang; Forné, Ignasi; Ammar, Constantin; et al.
Abstract : Background: Amino acid metabolism is crucial for inflammatory processes during atherogenesis. The endogenous amino acid homoarginine is a robust biomarker for cardiovascular outcome and mortality with high levels being protective. However, the underlying mechanisms remain elusive. We investigated the effect of homoarginine supplementation on atherosclerotic plaque development with a particular focus on inflammation. Methods: Female ApoE-deficient mice were supplemented with homoarginine (14 mg/L) in drinking water starting 2 weeks before and continuing throughout a 6-week period of Western-type diet feeding. Control mice received normal drinking water. Immunohistochemistry and flow cytometry were used for plaque- and immunological phenotyping. T cells were characterized using mass spectrometry–based proteomics, by functional in vitro approaches, for example, proliferation and migration/chemotaxis assays as well as by super-resolution microscopy. Results: Homoarginine supplementation led to a 2-fold increase in circulating homoarginine concentrations. Homoarginine-treated mice exhibited reduced atherosclerosis in the aortic root and brachiocephalic trunk. A substantial decrease in CD3 + T cells in the atherosclerotic lesions suggested a T-cell–related effect of homoarginine supplementation, which was mainly attributed to CD4 + T cells. Macrophages, dendritic cells, and B cells were not affected. CD4 + T-cell proteomics and subsequent pathway analysis together with in vitro studies demonstrated that homoarginine profoundly modulated the spatial organization of the T-cell actin cytoskeleton and increased filopodia formation via inhibition of Myh9 (myosin heavy chain 9). Further mechanistic studies revealed an inhibition of T-cell proliferation as well as a striking impairment of the migratory capacities of T cells in response to relevant chemokines by homoarginine, all of which likely contribute to its atheroprotective effects. Conclusions: Our study unravels a novel mechanism by which the amino acid homoarginine reduces atherosclerosis, establishing that homoarginine modulates the T-cell cytoskeleton and thereby mitigates T-cell functions important during atherogenesis. These findings provide a molecular explanation for the beneficial effects of homoarginine in atherosclerotic cardiovascular disease.